Radiation-Induced Phenomena in Wide-Gap Laser Materials Used in High-Radiation Areas - Harutyunyan, V. V.; Aleksanyan, E. M.; Arzumanyan, V. V.; Badalyan, A. O.
The analysis of the surface states in experimental reflection spectra is carried out peculiarities of the formation of defects of the electronic structure of irradiation corundum crystals is considered. It is shown that change of crystals reflectional ability is related to radiative growth forced by aluminum ions. The processes of radiative growth depend on the type and energy of irradiating high-energy particles. Kinetic of that growth is presented, which relates the intensity of zones with free aluminum ions to the concentration of such zones in near-surface layer.
Keywords: Physics